Design and development of novel Android 3D 3rd person shooting game - Kim On Chin; Syukri Majdi Hamdan; Tan Tse Guan (2018)
In recent years, smartphones have grown exponentially in popularity, taking over the world by storm. While the mobile gaming industry has grown large due to the development, there is a deluge of mediocre games in the Android market which replicate the same formulas of popular games. Thus, it motivates us to try at a new game development and design. The Android game is developed using the jMonkeyEngine game engine for Android 2.2 versions and above. It utilizes simple 3D graphics, and use the accelerometer and touch screen for input. It is single one on one battle against an AI enemy, which uses a simple finite state machine and viewed using a third-person camera that stays behind the player’s character and follows the enemy’s movements. We believes that the virtual joystick, a popular method of control in current games is inadequate for use as a control method to control the player character in a 3D third-person game. As such the accelerometer is being used as the game’s method of control, which is not only more sensitive and removes unneeded elements on the screen, but also to increase the game’s uniqueness. The project is developed using a test-driven process model. The system could be divided into three sections. A section of the code handles the generation of the character models and others, while an input handling system take care of mapping the player’s inputs to the correct responses. A 3D world is created, its members positioned correctly to form the ground, walls, and the player and enemy characters. Next, physics was added to the 3D objects so that they may interact with each other. Next came the implementation of the accelerometer to move the character around, and the touch screen to produce actions. Finally, a state machine is built for the game AI and suitable actions for each state is coded in. The game is tested via test runs as each functionality was implemented.